Outcome of self administered medical abortion pills by patients - Goyal, Neelam; Goyal, Sanjay Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Study of complication rate in patients presenting in Gynaec OPD after consuming self-prescribed medical abortion pills for unwanted pregnancies. Unchecked sale of Mifepristone and Misoprostol from pharmacies without prescription is giving rise to new emergencies in Gyn and Obs OPDs, which need to be urgently looked after by the authorities and public awareness regarding it’s abuse. Methods: 200 patients of reproductive age group from 17 yrs to 42 yrs over a period of 2 years from Apr 2014-Apr. 2016, who presented after consuming abortion pills, themselves, purchased over the counter from various pharmacies. Presenting complaints and complications were recorded and procedures required were analysed. Results: Significant percentage of patients landing into severe anemia, sepsis, incomplete abortions. Two patients required surgery for ruptured ectopic and one diagnosed as hydatiform mole, 3 pregnancies continued to second trimester. Conclusions: The high rate of medical complications occurring due to absence of medical surveillance of such patients and due to lack of protocol of Gynaec examination and ultrasound, it is highly recommended to have a better control over the unabated sale of these drugs at the pharmacies.